Synchronization investigation of vibration system of two co-rotating rotor with energy balance method. (19th January 2016) - Hou, Yongjun; Fang, Pan; Nan, Yanghai; Du, Mingjun
The key technology of vibrating screens' design is how to ascertain the synchronous state of vibrating systems. The occurrence of synchronization of a model, two co-rotating rotors fast excited by induction motors installed in a vibrating body, is treated in this article. The synchronization condition and stability criterion of the system are first derived by the energy balance method. The synchronization zones and stable phase difference are then estimated by the two co-rotating rotors operated in synchronous state. Moreover, the energy balance mechanism of the system is explained. The transfer of energy between the rotors by the vibrating body is presented as well. Finally, numerical studies of the dynamics are performed by Runge–Kutta method to verify the theoretical analysis. The results indicated that the synchronous state of the vibrating system is mainly determined by installation distance coefficient rl, installation angular β, symmetric coefficient δ, and electromagnetic torque Tei, but little influenced by mass ratios η and rm .